The Estimation of risk factors affecting patients associated with bronchial asthma in Basrah, southern Iraq: Case-control observational study. - Alsaimary, Ihsan Edan; Mezban, Falih Hmood (Jour Med Resh and Health Sci, 2021)
This study aimed to describe some of the risk factors of asthma in Basra south in Iraq; The study showed that (3,5) age group population were more affected with asthma (27.9%) and the Females were more affected than males in group 2,3and 5 (6.4%,15.7% and 14.7%)respectively compared to( 4.9%, 12.3% and 13.2) .In same group of male. While There were (68.6%) of patients came from urban areas in comparison to (31.4%) of cases who came from rural areas. The Smoking patients with positive (43.1%). and well patients with animal contact positive their proportion was while (49%). Seasonal asthma attack in male (23.5%) more than female (20.6%) the perennial asthma attach was recorded in male (29%) more than female (26.9%) in this study show Asthmatic patients with other allergy about (15.7%) and with chronic diseases (31.9%). The percentage of patients with positive family history were 39.2% of the cases.